Understanding Holistic Transformative Learning Based on Virtuous Values and Islamic Teachings - Aulia, Syifa Siti; Arpannudin, Iqbal; Sulisworo, Dwi (The Indonesian Institute of Science and Technology Research, 2025)
This article explores the concept of holistic, transformative learning, with an emphasis on virtuous values and Islamic teachings. In an era of rapid globalisation, education must evolve beyond mere academic performance to include character development, moral values, and social responsibility. By integrating the principles of virtue and Islamic ethics into education, a more comprehensive model of learning is proposed, one that balances intellectual, emotional, social, and spiritual growth. This study aims todiscussesportance of holistic education in the Indonesian context, its global relevance, the opportunities and challenges it presents, and the necessary skills for becoming a responsible global citizen. The article also highlights how Islamic values contribute to shaping well-rounded individuals who are equipped to tackle modern societal issues while fostering global cooperation.